Acute rejection in cadaveric renal transplantation under cyclosporine based therapy. Analysis of the risk factors and its influence on chronic dysfunction. - Mota, Alfredo (Acta Médica Portuguesa, 2004)
The aim of this study was to study the incidence and causes of acute rejection (AR) on cadaveric renal transplants under cyclosporine A-based immunosuppression, and to investigate the AR effect on the ocurrence of chronic dysfunction (CD) and on the outcome of transplantation.We analyzed 794 renal transplants from cadaver donor between December, 1985 and December, 1999. We examined the major donor, recipient and graft-related factors and their influence in graft outcome. The diagnosis of AR was in 65% based in clinical and laboratorial findings: fever, decrease of diuresis, graft pain and/or strained and a serum creatinine increase of at least 0,4 mg/dl, and in 35% the diagnosis of AR was biopsy-proven. Statistics included univariate and multivariate analysis. Graft and patient survival rates were calculated by Kaplan-Meier method (with log-rank test).In the 794 renal transplants included in the study, 498 (63%) didn’t have AR and 296 (37%) had at least one episode of AR. This overall incidence of AR of 37% is decreasing and in the last two years, 1998 and 1999 remained in 24% and 25%, respectively. The AR was associated with cadaver donor-related factors [ non traumatic cause of death (p=0,018), perfusion with Eurocollins solution (p=0,008) and cold ischemia time > 24 hours (p= 0,032)] and with recipient-related factors [age < 45 years (p=0,000) and immunosuppression with antithymocyte globulin (ATG) + azathioprine (Aza) + prednisone (Pred) + cyclosporine A (CsA) (p=0,006)]. Concerning graft-related factors acute tubular necrosis (ATN) was related with higher incidence of AR (35% of AR without ATN versus 48% of AR with ATN, p= 0,008) and this, was responsible by a significative increase of chronic dysfunction (CD) (p= 0,000) and by the worst graft function at the end of the first year (p= 0,000). Our results also showed that CD as a cause of graft loss increased substantially (23% vs 49%) in the presence of AR. The 1, 3, 5, 10 and 15-year graft survival in the patients with AR were, 94%, 85%, 74%, 50% and 38%, respectively, and in the patients without AR, 97%, 91%, 87%, 77% and 67%, respectively. These results were statistically significant ( p= 0,000). The AR didn’t influence patient survival (p= 0,814).Our overall incidence of AR (37%) is decreasing reaching in the last year 25%. The AR incidence increased significantly with grafts from cadaver donors with non-traumatic cause of death, preserved with Eurocollins solution, with cold ischemia times > 24 hours and in recipients with age < 45 years and with ATG+Aza+Pred+CsA immunosuppression regimen. ATN increased the AR incidence and this was associated with a higher ocurrence of CD and a worst graft function at 1 year. The graft lost by CD duplicate in the patients with AR. Graft survival was significantly worse in the patients with AR. The AR did not adversely affect patient survival.